Pengaruh Kualitas Pelayanan Terhadap Loyalitas Pelanggan Pada PT. Pelabuhan Indonesia II (Persero) Cabang TJ. Priok - Shiddiq Maulana Ibrahim; Siti Sahara (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This study aims to analyze the effect of service quality on customer loyalty at PT. Pelabuhan Indonesia II (Persero) Tanjung Priok Branch. This study used a survey method with questionnaires as a data collection instrument that was disseminated to customers of PT. Pelabuhan Indonesia II (Persero) Tanjung Priok Branch. Service quality is measured through various dimensions such as responsiveness, reliability, assurance, empathy, and physical evidence. While customer loyalty is assessed through aspects of loyalty, recommendations to others, and intensity of service use. Data analysis was conducted using regression techniques to determine the extent to which service quality contributes to customer loyalty. The results of this study are expected to provide a clear picture of the factors that influence customer loyalty in the service industry and provide recommendations for improving service quality to maintain and increase customer loyalty at PT. Pelabuhan Indonesia II (Persero) Tanjung Priok Branch.